Effect of Electronic Health Record Prompts on the Frequency of Blood Lead Tests - Anna E. Kellund; Roland C. Hentz; Valeria Cristiani; Brian A. Lynch (SAGE Publishing, 2023)
Introduction/Objectives: Elevated blood lead levels can cause impaired cognition and behavioral problems in children. Screening is important for identifying children with elevated blood lead levels, but many children who qualify for screening do not get tested. We aimed to see if the addition of prompts in the electronic health record (EHR) would lead to differences in blood lead tests ordered for children with government insurance. Methods: In May 2018, a prompt was added to our institutional EHR that reminded primary care practitioners to recommend lead testing for patients with government insurance. For this retrospective observational pre-post comparative study, we reviewed the rate of blood lead test orders and completed collection before and after the prompt was introduced. Results: The number of blood lead tests ordered did not increase after prompts were introduced in the EHR; rather, the lead screening rates at 12-month well-child visits decreased from 63.6% to 53.8% ( P  = .008). The 24-month visit data did not change significantly for the number of lead tests ordered before and after the prompt was introduced in the EHR. The number of lead tests completed showed a significant decrease after the prompt was introduced for the 12-month visit ( P  < .001) but no significant change for the 24-month visit ( P  = .70). Conclusions: This study showed that the addition of prompts in the EHR was not associated with an increase in the number of blood lead level tests ordered. Further research is needed to determine factors that could affect lead screening rates.